Complex spatio-temporal structure of the Holocene Thermal Maximum - Cartapanis, Olivier; Jonkers, Lukas; Moffa-Sanchez, Paola; Jaccard, Samuel L.; De Vernal, Anne (Nature Communications, 2022)
Abstract Inconsistencies between Holocene climate reconstructions and numerical model simulations question the robustness of climate models and proxy temperature records. Climate reconstructions suggest an early-middle Holocene Thermal Maximum (HTM) followed by gradual cooling, whereas climate models indicate continuous warming. This discrepancy either implies seasonal biases in proxy-based climate reconstructions, or that the climate model sensitivity to forcings and feedbacks needs to be reevaluated. Here, we analyze a global database of Holocene paleotemperature records to investigate the spatiotemporal structure of the HTM. Continental proxy records at mid and high latitudes of the Northern Hemisphere portray a “classic” HTM (8–4 ka). In contrast, marine proxy records from the same latitudes reveal an earlier HTM (11–7ka), while a clear temperature anomaly is missing in the tropics. The results indicate a heterogeneous response to climate forcing and highlight the lack of globally synchronous HTM.

Palaeoclimate constraints on the impact of 2 °C anthropogenic warming and beyond - Fischer, Hubertus; Meissner, Katrin J.; Mix, Alan C.; Abram, Nerilie J.; Austermann, Jacqueline; Brovkin, Victor; Capron, Emilie; Colombaroli, Daniele; Daniau, Anne-Laure; Dyez, Kelsey A.; Felis, Thomas; Finkelstein, Sarah A.; et al. (Nature Geoscience, 2018)